The Effect of Social Mobility to Disfigure Houses Elevations - Al-Ataabi, Mahdi Saleh; Alhelli, Ali Adnan Alwan (Iraqi Journal of Architecture and Planning, 2017)
Architecture is a mutual dialogue system where the place and time interact with environment. However, when noises interfere with this process, the architecture system will lose its mutual dialogue, which prevent society such an important communicating tool with world. Therefore, the objective of this article is to declare the effect of the society trends system changes in deforming the signification system that produce architectural forms, that lead to disfigurement of architecture. The research problem is “the Social mobility is associated with a signification system changes and appearance of disfigurement. We suppose that the social mobility push the architecture of society to Integrate in new environment through physical copying of the available forms without intellectual values projecting own intellectual values on these forms resulting in separating the matter system from the signification system which make the form disfigured. We choose holy Karbala houses as a case study as Karbala city has a great place in history and Islamic religion that make its architecture face the effect of too many waves of social mobility throughout history. We conclude that the disfigured architecture is not durable because it disappears with time when their own secondary social and intellectual behaviours are retouched. On the other hand, most cities can be divide in to 3 reigns and the disfigurement is a result of the intersection between these reigns.